Unleashing Animal Spirits: Self-Control and Overpricing in Experimental Asset Markets - Kocher, Martin G; Lucks, Konstantin E; Schindler, David (Review of Financial Studies, 2019)
One explanation for overpricing on asset markets is a lack of traders' self-control. Self-control is the individual capacity to override or inhibit undesired impulses that may drive prices. We implement the first experiment to address the causal relationship between self-control abilities and systematic overpricing on financial markets. Our setup can detect some of the channels through which individual self-control restrictions could transmit into irrational exuberance in markets. Our data indicate a large direct effect of restricted self-control abilities on market overpricing. Low self-control traders report stronger emotions after the market.